Analisis Kinerja Keuangan Dengan Menggunakan Metode Value For Money Pada Badan Pengelola Keuangan Dan Aset Daerah Kabupaten Sikka - Adriana Alesandra Da Cunha; Henrikus Herdi; Pipiet Niken Aurelia (Universitas Maritim AMNI Semarang, 2023)
This study aims to determine and analyze financial performance using the value for money method of the Sikka Regency Regional Financial and Asset Management Agency. This type of research is descriptive quantitative. The data used is secondary data. Data collection techniques using literature and documentation. The data analysis used is quantitative analysis using the value for money method based on three elements, namely economy, efficiency and effectiveness. The results of the study show that the financial performance of the Sikka Regency Regional Financial and Asset Management Agency for the 2019-2021 fiscal year, when viewed from an economic level, is categorized as economical because the economic ratio level is less than 100%. Judging from the level of efficiency, the 2019-2021 fiscal year is categorized as efficient because the efficiency ratio is less than 100%. In terms of the level of effectiveness for the 2019 and 2021 fiscal years, they are categorized as ineffective because the effectiveness ratio is less than 100% and 2020 is categorized as effective because the effectiveness ratio is more than 100%.